2011
DOI: 10.1210/en.2010-1462
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Foxd3 Results in Decreased β-Cell Proliferation and Glucose Intolerance During Pregnancy

Abstract: A complete molecular understanding of ␤-cell mass expansion will be useful for the improvement of therapies to treat diabetic patients. During normal periods of metabolic challenges, such as pregnancy, ␤-cells proliferate, or self-renew, to meet the new physiological demands. The transcription factor Forkhead box D3 (Foxd3) is required for maintenance and self-renewal of several diverse progenitor cell lineages, and Foxd3 is expressed in the pancreatic primordium beginning at 10.5 d postcoitum, becoming locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 72 publications
1
40
0
6
Order By: Relevance
“…Literature have demonstrated that FOXD3 is required for the maintenance and self-renewal of the neural crest progenitors [32,33]. Loss of FOXD3 may lead to a decrease in b-cell proliferation [34], while SOX10 depletion may inhibit cell proliferation [35]. In our study, fibroblasts transfected by FOXD3 plasmids showed higher proliferation rate than those without transfection.…”
Section: Discussionsupporting
confidence: 52%
“…Literature have demonstrated that FOXD3 is required for the maintenance and self-renewal of the neural crest progenitors [32,33]. Loss of FOXD3 may lead to a decrease in b-cell proliferation [34], while SOX10 depletion may inhibit cell proliferation [35]. In our study, fibroblasts transfected by FOXD3 plasmids showed higher proliferation rate than those without transfection.…”
Section: Discussionsupporting
confidence: 52%
“…This notion that transcription factors can have temporally separated effects on cell behavior is not novel, as deletion of Hnf4α in the embryonic liver affects gene expression in differentiated hepatocytes long after its expression is down-regulated (Kyrmizi et al, 2006). Similarly, the FoxD3 transcription factor, which is expressed in adult, quiescent β cells is required for β-cell proliferation during pregnancy despite being absent from maternal β cells during pregnancy (Plank et al, 2011). Our preferred model is that Pdx1 and Oc1 cooperate in multi- or bi-potent pancreatic progenitors to establish a competency state that is realized in later stages of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent changes in blood glucose were measured at 15-, 30-, 60-, 90-, and 120-min intervals following injection; n ϭ 3 (weeks 3, 7, and 9) or 6 (weeks 1, 5, and 11). Plasma insulin assays were performed as described in (31), with the modification that blood was harvested from the saphenous veins of 16-h-fasted animals using heparinized Natelson bloodcollecting tubes (Kimble Chase, Rockwood, TN).…”
Section: Methodsmentioning
confidence: 99%